2022
DOI: 10.1002/adom.202201188
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Voltage Electrically Responsive Photonic Crystal Based on Weak‐Polar Colloidal System

Abstract: Electrically responsive photonic crystal (ERPC) based on particle electrophoresis is a promising material to construct reflective color displays with low‐power‐consumption and antiglare advantages. However, the high driving voltages for the polar ERPC inevitably cause electrochemical reactions on the electrode, which decreases the stability and reversibility of electrical response. Here, a weak‐polar EPRC composed of hydrophobic SiO2 particles, 1,2‐dichlorobenzene (DCB), and dioctyl sulfosuccinate sodium salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…This is a common limitation for known low-voltage ERPCs. 4 Typically, it took about 45 s and 90 s for the ERPC to achieve its balanced optical signal when a voltage of 0.8 V was directly applied to or withdrawn from the SiO 2 /ANI ERPC (Fig. S13a, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a common limitation for known low-voltage ERPCs. 4 Typically, it took about 45 s and 90 s for the ERPC to achieve its balanced optical signal when a voltage of 0.8 V was directly applied to or withdrawn from the SiO 2 /ANI ERPC (Fig. S13a, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…Various stimuli, including electric field, [1][2][3][4][5][6][7] magnetic field, [8][9][10][11] thermal interaction, [12][13][14] mechanical force, [15][16][17] and the chemical environment, [18][19][20][21][22][23][24] are capable of changing the color of photonic crystals. Considering the feasibility of controlling the electric field on a miniaturized scale, an electrically responsive photonic crystal (ERPC) was an ideal system for realizing instant and accurate tuning of colors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Ge and co-workers recently reported that a weak-polar medium can enhance voltage response of electrically responsive photonic crystal. [12] They also investigated a bistable EPD which is suitable for a low-power consumption display. [13] Microencapsulation of particle dispersion is a prerequisite to expediting the commercialization of color EPD, as the microcapsule (μ-capsule) is an ideal form for the EPD material, which can be coated on the transparent electrode with no leakage concern.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Ge and co‐workers recently reported that a weak‐polar medium can enhance voltage response of electrically responsive photonic crystal. [ 12 ] They also investigated a bistable EPD which is suitable for a low‐power consumption display. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%